Incorporation of manganese carbonyl sulfide ((Mn2S2 (CO)7) and mixed metal oxides-decorated reduced graphene oxide (MnFeCoO4/rGO) as a selective anode toward efficient OER from seawater splitting under neutral pH conditions. (May 2022) - Ghouri, Zafar Khan; Elsaid, Khaled; Mahmoud Nasef, Mohamed; Badreldin, Ahmed; Wubulikasimu, Yiming; Abdel-Wahab, Ahmed
Abstract: Applying non-noble metal-based electrocatalysts toward efficient and cost-effective oxygen evolution reaction (OER) from seawater under mild pH conditions are of paramount importance for advancing green hydrogen production through renewable energy. Amongst several predicaments, the presence of chloride ions in seawater competes with the OER as a more kinetically facile anodic reaction that results in the formation of toxic chlorine products. Herein, we propose a novel material combination, which exhibits higher OER activity and selectively over chlorine evolution reaction (CER) during simulated saline water electrolysis under neutral pH conditions. The proposed hybrid nanocomposite system, based on electroactive mixed metal oxides-decorated reduced graphene oxide (MnFeCoO4 /rGO) which is incorporated with manganese carbonyl sulfide (Mn2 S2 (CO)7 ), are fabricated by a single-step hydrothermal technique. Benefiting from their heterogeneous interfaces, lower charge transfer resistance, and higher electrochemical (EC) and BET surface area, the hybrid graphene MnFeCoO4 /Mn2 S2 (CO)7 nanocomposite (HGNC) yields the best performance among various options towards OER from pH-neutral seawater (1 M PB + 0.6 M NaCl; pH 7.0) electrolysis, with small Tafel slope of 74.1 mVdec −1 and correspondingly low overpotential of ∼310 mV to achieve a current density of 10 mAcm −2 . The high activity at the aforementioned current density allows for overpotential operation below the minimum thermodynamic requirement needed for activating CER, thus ruling out progression of CER. Further, benefiting from the strong coupling effect between the MnFeCoO4 /Mn2 S2 (CO)7 species and the graphene support, appreciable stability was achieved for 15 h to deliver steady-state current stability without obvious decay, which demonstrating that HGNC is a promising candidate as an OER electrocatalyst for neutral seawater electrolysis.